Nitric oxide (NO) photo-release in a series of ruthenium–nitrosyl complexes: new experimental insights in the search for a comprehensive mechanism. (7th December 2018) - Roose, Max; Tassé, Marine; Lacroix, Pascal G.; Malfant, Isabelle
Abstract : The mechanism of nitric oxide release is investigated along a series of 1–3 "push–pull" ruthenium nitrosyl complexes. Abstract : A series of four ruthenium(ii ) complexes built from the [Ru(terpy)(bipy)(NO)] 3+ core (terpy is 2, 2′:6′, 2′′-terpyridine and bipy is 2, 2′-bipyridine) are investigated. They differ by the presence of zero, one, two, or three 4′-(4-methoxyphenyl) (MP) electron donor substituents introduced at different positions on the pyridine fragments to increase the intramolecular charge transfer capabilities towards the strongly withdrawing nitrosyl (NO) ligand. The UV-visible spectra reflect the presence and position of the MP substituents on the complexes. In the case of species containing the 4′-(MP)-terpy ligand, a low-lying transition is identified as arising from 4′-(MP)-terpy to Ru(NO) intramolecular charge transfer, which is further confirmed by TD-DFT analysis. Irradiation performed at λ = 436 nm on this isolated transition for different complexes leads to quantum yields of NO photo-release equal to 0.002 and 0.011, in a ratio of 6 (instead of 1), which allows concluding non-ambiguously that a single electron transition cannot account for the NO release mechanism.